"I'll take them another day": A qualitative study exploring the socio-behavioral complexities of childhood vaccination in urban poor settlements. - Judy Gichuki; Ben Ngoye; Francis Wafula (PLoS ONE)
Despite improvement over recent decades, childhood vaccination uptake remains a concern across countries. The World Health Organization observed that over 25 million children missed out on one or more vaccines in 2021, with urban poor and other marginalized groups being the most affected. Given the higher risk of disease transmission and vaccine-preventable diseases (VPD) outbreaks across densely populated urban slums, identifying effective interventions to improve childhood vaccination in this vulnerable population is crucial. This study explored the behavioral and social factors influencing childhood vaccination uptake in urban informal settlements in Nairobi, Kenya. A grounded theory approach was employed to develop a theoretical account of the socio-behavioral determinants of childhood vaccination. Five focus group discussions (FGDs) were conducted with purposively sampled caregivers of children under five years of age residing in informal settlements. The Theory of Planned Behavior guided the structuring of the FGD questions. An iterative process was used to analyze and identify emerging themes. Thirty-nine caregivers (median age 29 years) participated in the FGDs. From the analysis, four main thematic categories were derived. These included attitude factors such as perceived vaccine benefits, cultural beliefs, and emotional factors including parental love. Additionally, subjective norms, like fear of social judgment, and perceived behavioral control factors, such as self-control and gender-based influences, were identified. Furthermore, a number of practical factors, including the cost of vaccines and healthcare providers attitude, also affected the uptake of vaccination. Various social, behavioral, cultural, and contextual factors influence caregiver vaccination decisions in urban poor settings. Community-derived and context-specific approaches that address the complex interaction between socio-behavioral and other contextual factors need to be tested and applied to improve the timely uptake of childhood vaccinations among marginalized populations.